2019
DOI: 10.1289/ehp5045
|View full text |Cite
|
Sign up to set email alerts
|

Proposed Key Characteristics of Male Reproductive Toxicants as an Approach for Organizing and Evaluating Mechanistic Evidence in Human Health Hazard Assessments

Abstract: Background:Assessing chemicals for their potential to cause male reproductive toxicity involves the evaluation of evidence obtained from experimental, epidemiological, and mechanistic studies. Although mechanistic evidence plays an important role in hazard identification and evidence integration, the process of identifying, screening and analyzing mechanistic studies and outcomes is a challenging exercise due to the diversity of research models and methods and the variety of known and proposed pathways for che… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
40
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(40 citation statements)
references
References 118 publications
0
40
0
Order By: Relevance
“…In 2016, the EPA completed a "Framework for Incorporating Human Epidemiologic & Incident Data in Risk Assessments for Pesticides" which noted that toxicology and risk assessment are undergoing transformational changes driven by new research [111]. One such development relevant to risk assessment is the identification of Key Characteristics applicable to endocrine disruption [112], male and female reproductive toxicity [113,114] and carcinogenesis [115,116]. The Key Characteristics approach highlighted the diversity of toxicity pathways that can lead from exposure to environmental contaminants to an elevated risk of disease.…”
Section: Discussionmentioning
confidence: 99%
“…In 2016, the EPA completed a "Framework for Incorporating Human Epidemiologic & Incident Data in Risk Assessments for Pesticides" which noted that toxicology and risk assessment are undergoing transformational changes driven by new research [111]. One such development relevant to risk assessment is the identification of Key Characteristics applicable to endocrine disruption [112], male and female reproductive toxicity [113,114] and carcinogenesis [115,116]. The Key Characteristics approach highlighted the diversity of toxicity pathways that can lead from exposure to environmental contaminants to an elevated risk of disease.…”
Section: Discussionmentioning
confidence: 99%
“…Alterations in cellular receptor signaling and subsequent changes in genomic and metabolic pathways controlled by those receptors have a profound influence on the development, and function of cells, tissues and organisms as well as on the risk of cancer and other diseases [6,142,143]. For example, exposure to xenobiotic substances that modulate estrogen and testosterone signaling pathways can influence breast and testicular cancer development [144][145][146][147].…”
Section: Modulates Receptor-mediated Effectsmentioning
confidence: 99%
“…Two papers recently published in Environmental Health Perspectives outlined this approach in identifying key characteristics of chemicals that cause reproductive toxicity in females 2 and males. 3 Identifying key characteristics enables toxicologists to flag chemicals that have qualities associated with specific forms of toxicity. In 2012, an international working group organized by the International Agency for Research on Cancer compiled the first list of key characteristics when they identified 10 properties shared by carcinogenic chemicals.…”
mentioning
confidence: 99%